Rice germplasm : (International Rice Research Institute, 1991)
The book collects paper on collecting, preserving, and using plant genetic resources. Authors are working together to facilitate dialogue on this issue, and collaborated in hosting the third international workshop on rice germplasm. A distinguished group of scientists from all over the world who are concerned with safeguarding the world’s rice germplasm participated. They vigorously discussed ideas and activities to foster the continuing exchange of germplasm. This is just part of their work to ensure that germplasm is always freely available